2020
DOI: 10.18502/ijph.v49i11.4720
|View full text |Cite
|
Sign up to set email alerts
|

The Necessity of Medical Humanities Education to General Practitioners: A Brief Review

Abstract: To the ultimate overall goal to train sufficient numbers of highly qualified general practitioners. We analyzed the recent study on the necessity of medical humanities education for general practitioners and the status of the humanities education of general practitioners. Meanwhile, the model of medical humanities education for general practitioners in China in the future is prospected, with the support of the general practice departments in comprehensive tertiary hospitals. Improving the training mode of gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
0
1
0
Order By: Relevance
“…In the document named “Opinions on reforming and improving the incentive mechanism of training and using general practitioners” issued by the General Office of the State Council, PRC on January 24, 2018, many preferential measures have been put forward for the career development of GPs based on salary and career planning, which has enhanced the sense of professional honor and adhered to the combination of spiritual rewards and material rewards. At present, most researchers are focusing on improving career growth and have summarized the correlated influencing factors from multiple perspectives ( Ellis et al, 2020 ; Harris et al, 2020 ; Zhao et al, 2020 ). In general, career growth is a dynamic development process that is influenced by values and systems, divided into psychological and organizational levels.…”
Section: Introductionmentioning
confidence: 99%
“…In the document named “Opinions on reforming and improving the incentive mechanism of training and using general practitioners” issued by the General Office of the State Council, PRC on January 24, 2018, many preferential measures have been put forward for the career development of GPs based on salary and career planning, which has enhanced the sense of professional honor and adhered to the combination of spiritual rewards and material rewards. At present, most researchers are focusing on improving career growth and have summarized the correlated influencing factors from multiple perspectives ( Ellis et al, 2020 ; Harris et al, 2020 ; Zhao et al, 2020 ). In general, career growth is a dynamic development process that is influenced by values and systems, divided into psychological and organizational levels.…”
Section: Introductionmentioning
confidence: 99%
“…The target population of standardized training is medical students, and the training focuses on basic theories, clinical skills, and primary medical and health practices [19,20]. In recent years, some scholars have proposed that humanistic quality should be added to the training, mainly starting from the physical and mental health of patients and paying attention to the correlation between humanistic emotion and management ability and the factors of patients' physiological attributes [21][22][23]. Some trainees reported that the level of professional knowledge and skills, teamwork, and learning ability has improved, and community health service capabilities have been improved [24,25].…”
Section: Introductionmentioning
confidence: 99%